THE POETRY FOR THE CHILDREN OF HACİ ÖMER LÜTFI - Çako, Tülay (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
Haci Ömer Lütfi, who occupies an important place in the Turkish literature of the former Yugoslavia, with his literary work left a mark on the period in which he lived, from the end of the XIX century to the beginning of the XX century. With all his works, he is considered an eminent poet from an aesthetic, historical and political point of view. Thanks to all its expressive qualities, sophistication of the language and mastery of the verses, it brought new contemporary elements to Turkish literature, which was rooted in Yugoslavia and before it. Throughout his creative life, Omer Lutfi has written about sixty prose and poetic works that mainly contain elements of religion, politics and history. However, so far no separate reviews and studies of his valuable works have been made, except for some estimates and predictions. In addition to his numerous literary works, Omer Lutfi has written 7 poems for children belonging to Turkish children’s literature in the former Yugoslavia, and thanks to these children’s poems so far he has been considered the first Turkish poet for children and the founder of the children’s literature in Turkish language in the former Yugoslavia. Keywords: Haci Ömer Lütfi; literature for children in Turkish language; poems for children in Turkish language.